LABA AKUNTANSI TERHADAP PENGUNGKAPAN ISLAMIC SOCIAL REPORTING (ISR) DENGAN AKUNTABILITAS SEBAGAI PEMODERASI PADA PERBANKAN SYARIAH YANG TERDAFTAR DI BEI - Kiki Halida Batubara; Afrah Junita; Muhammad Salman; Rahmad Tantawi (Jurnal Mahasiswa Akuntansi Samudra, 2023)
This research aims to determine the effect of financial performance on Islamic Social Reporting (ISR) disclosure with accountability as a moderator in sharia banking listed on the Indonesia Stock Exchange. The population in this research is all sharia banking companies listed on the Indonesia Stock Exchange in 2010-2019. Sample selection was carried out using purposive sampling and obtained 4 sharia banking companies listed on the Indonesia Stock Exchange in 2010-2019. The data analysis methods used are classic assumption tests such as: data normality test, multicollinearity test, autocorrelation test and heteroscedasticity test as well as hypothesis tests such as multiple linear regression tests, interaction tests or what is usually called Moderated Regression Analysis (MRA), t test ( partial test), F test (simultaneous test) and coefficient of determination test (R2 test). The research results show that partially, financial performance has no significant effect on Islamic Social Reporting (ISR) disclosure, Accountability has a significant effect on Islamic Social Reporting (ISR) disclosure. Meanwhile, based on the Moderated Regression Analysis (MRA) test, accountability cannot partially moderate the influence of financial performance on Islamic Social Reporting (ISR) disclosures and simultaneously accountability can moderate the influence of financial performance on Islamic Social Reporting (ISR) disclosures.